2022
DOI: 10.1530/etj-21-0054
|View full text |Cite
|
Sign up to set email alerts
|

Tissue sensitivity to thyroid hormones may change over time

Abstract: Introduction: Patients with congenital hypothyroidism (CH) may transiently show a certain degree of pituitary resistance to levothyroxine (LT4) which, however, normalizes subsequently. However, in some individuals TSH fails to normalize despite adequate LT4 treatment. Methods: Nine patients with CH followed in three Academic Centre who developed over time a resistance to thyroid hormones underwent extensive biochemical and genetic analyses. These latter were performed by Sanger sequence or targeted Next Gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Considering that the secretory capacity of the thyroid gland (the SPINA-GT index) seemed unaffected in the CFS patients, the suppressed serum T3 to T4 ratio in SELENOP-aAb positive patients is compatible with a defect in local deiodination of TH in Se-sensitive target tissues, like brain, bone, skeletal muscle and others [ 39 , 52 ]. This interpretation is supported by the hypothyroid-like clinical characteristics of , and it is tempting to speculate that SELENOP-aAb lead to an acquired form of resistance to thyroid hormone (A-RTH) with impaired local activation of T4 to T3 [ 53 , 54 ]. Collectively, the physiological consequences from SELENOP-aAb that can be deduced from the data would predict intracellular Se deficiency, low GPx and DIO biosynthesis rate, impaired TH activation in SELENOP-target cells with local hypothyroidism, reduced iodide liberation causing low urinary iodine, and elevated oxidative stress in kidney and elsewhere ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Considering that the secretory capacity of the thyroid gland (the SPINA-GT index) seemed unaffected in the CFS patients, the suppressed serum T3 to T4 ratio in SELENOP-aAb positive patients is compatible with a defect in local deiodination of TH in Se-sensitive target tissues, like brain, bone, skeletal muscle and others [ 39 , 52 ]. This interpretation is supported by the hypothyroid-like clinical characteristics of , and it is tempting to speculate that SELENOP-aAb lead to an acquired form of resistance to thyroid hormone (A-RTH) with impaired local activation of T4 to T3 [ 53 , 54 ]. Collectively, the physiological consequences from SELENOP-aAb that can be deduced from the data would predict intracellular Se deficiency, low GPx and DIO biosynthesis rate, impaired TH activation in SELENOP-target cells with local hypothyroidism, reduced iodide liberation causing low urinary iodine, and elevated oxidative stress in kidney and elsewhere ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The NKX2-5 gene is a member of the homeobox Nkx2 family that has been implicated in the pathogenesis of CH [25]. TSHB encodes the beta subunit of thyroid-stimulating hormone and a reduced methylation status at this level might favor the circulating TSH rise in CH patients and potentially explain the relative pituitary refractoriness in the normalization of circulating TSH occurring in some patients with CH during levothyroxine replacement [26][27][28][29].…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, they propose combined replacement therapy with T4 + T3 (55). Some of the patients reported by Lacámara were affected with congenital hypothyroidism (CH) and indeed earlier studies found that in 10-40% of neonates and children with CH the TSH fails to normalize despite an adequate LT4 treatment (56,58). In addition, a still unexplained degree of resistance to levothyroxine (LT4) persists also later in life, as adult CH patients maintain euthyroidism with higher L-T4 doses compared to postsurgical acquired hypothyroidism (59).…”
Section: Resistance To Exogenous Thyroxine (Reth)mentioning
confidence: 99%